Specialized nucleoprotein structures at the origin of replication of bacteriophage lambda: localized unwinding of duplex DNA by a six-protein reaction. - Dodson, M (1986)
The O protein of bacteriophage lambda localizes the initiation of DNA replication to a unique site on the lambda genome, ori lambda. By means of electron microscopy, we infer that the binding of O to ori lambda initiates a series of protein addition and transfer reactions that culminate in localized unwinding of the origin DNA, generating a prepriming structure for the initiation of DNA replication. We can define three stages of this prepriming reaction, the first two of which we have characterized previously. First, dimeric O protein binds to multiple DNA binding sites and self-associates to form a nucleoprotein structure, the O-some. Second, lambda P and host DnaB proteins interact with the O-some to generate a larger complex that includes additional DNA from an A + T-rich region adjacent to the O binding sites. Third, the addition of the DnaJ, DnaK, and Ssb proteins and ATP results in an origin-specific unwinding reaction, probably catalyzed by the helicase activity of DnaB. The unwinding reaction is unidirectional, proceeding "rightward" from the origin. The minimal DNA sequence competent for unwinding consists of two O binding sites and the adjacent A + T-rich region to the right of the binding sites. We conclude that the lambda O protein localizes and initiates a six-protein sequential reaction responsible for but preceding the precise initiation of DNA replication. Specialized nucleoprotein structures similar to the O-some may be a general feature of DNA transactions requiring extraordinary precision in localization and control.